Contingency management in three psychology courses a case report - Decenteceo, Edwin T. (Philippine Journal of Psychology, 1972)
This paper reports a method of handling classes on the basis of the findings and developments in the experimental analysis of behavior. The main contingency for reinforcement consisted of the mastery of a given section of the course material as indicated by a student's performance in an examination, whereupon the student was assigned another section to study. Response units which the students could easily handle were used and mastery of each response unit was required before the next unit was introduced. Aversive situations were kept at a minimum and the reinforcements in the form of student's scores were given almost immediately. A description of the contingency applied to three classes is reported and the corresponding results as reflected by grades are compared.